Ultrafast dynamics and scattering of protic ionic liquids induced by XFEL pulses. (19th August 2021) - Patra, Kajwal Kumar; Eliah Dawod, Ibrahim; Martin, Andrew V.; Greaves, Tamar L.; Persson, Daniel; Caleman, Carl; Timneanu, Nicusor
Abstract : This radiation damage study uses a hybrid approach combining molecular dynamics with non‐thermal plasma simulations to follow the femtosecond dynamics and X‐ray scattering from a protic ionic liquid as it is investigated by an intense XFEL pulse. Abstract : X‐rays are routinely used for structural studies through scattering, and femtosecond X‐ray lasers can probe ultrafast dynamics. We aim to capture the femtosecond dynamics of liquid samples using simulations and deconstruct the interplay of ionization and atomic motion within the X‐ray laser pulse. This deconstruction is resolution dependent, as ionization influences the low momentum transfers through changes in scattering form factors, while atomic motion has a greater effect at high momentum transfers through loss of coherence. Our methodology uses a combination of classical molecular dynamics and plasma simulation on a protic ionic liquid to quantify the contributions to the scattering signal and how these evolve with time during the X‐ray laser pulse. Our method is relevant for studies of organic liquids, biomolecules in solution or any low‐ Z materials at liquid densities that quickly turn into a plasma while probed with X‐rays.